2012
DOI: 10.1098/rsif.2012.0271
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of human mesenchymal stem cells to vibration and cold storage conditions representative of cold transportation

Abstract: In the current study, the mechanical and hypothermic damage induced by vibration and cold storage on human mesenchymal stem cells (hMSCs) stored at 2-88C was quantified by measuring the total cell number and cell viability after exposure to vibration at 50 Hz (peak acceleration 140 m s 22 and peak displacement 1.4 mm), 25 Hz (peak acceleration 140 m s 22, peak displacement 5.7 mm), 10 Hz (peak acceleration 20 m s 22, peak displacement 5.1 mm) and cold storage for several durations. To quantify the viability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 54 publications
(83 reference statements)
0
23
0
Order By: Relevance
“…Mechanical forces have been shown to affect MSC differentiation potential (Wang and Chen, 2013) and Nikolaev et al, (2012) showed that under hypothermic conditions, human MSCs were sensitive to vibrations that mimicked road transportation of cells suspended in vials. They reported that cells that had already been stored at 4…”
Section: Can the Cell Therapy Be Transported?mentioning
confidence: 99%
“…Mechanical forces have been shown to affect MSC differentiation potential (Wang and Chen, 2013) and Nikolaev et al, (2012) showed that under hypothermic conditions, human MSCs were sensitive to vibrations that mimicked road transportation of cells suspended in vials. They reported that cells that had already been stored at 4…”
Section: Can the Cell Therapy Be Transported?mentioning
confidence: 99%
“…Bone marrow derived stem cells show sensitivity to vibrations (Zhou et al 2011) and a study by Nikolaev et al (2012) found a coupling effect between vibration and cold temperature storage. Mechanical stress during the transportation process requires further investigation to elucidate the effects on cell health and function and to help design appropriate packaging which is sustainable and cost effective whilst maintaining the therapeutic quality of cells (Nikolaev et al 2012). …”
Section: Challengesmentioning
confidence: 99%
“…Stem cells are sensitive even with vibration and under cold storage conditions [37]. Therefore, in case of HA-PVPA injectable hydrogel sustain stem cells, it will probably proliferate and able to differentiate into other cell-lines [38].…”
Section: Pvpamentioning
confidence: 99%